2018
DOI: 10.1016/j.bbalip.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 4,5-bisphosphate, cholesterol, and fatty acids modulate the calcium-activated chloride channel TMEM16A (ANO1)

Abstract: The TMEM16A-mediated Ca-activated Cl current drives several important physiological functions. Membrane lipids regulate ion channels and transporters but their influence on members of the TMEM16 family is poorly understood. Here we have studied the regulation of TMEM16A by phosphatidylinositol 4,5-bisphosphate (PI(4,5)P2), cholesterol, and fatty acids using patch clamp, biochemistry and fluorescence microscopy. We found that depletion of membrane PI(4,5)P2 causes a decline in TMEM16A current that is independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
66
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 89 publications
5
66
1
Order By: Relevance
“…A typical PM anchor is PI(4,5)P 2 , and the ANO8 yeast homologue Ist2 has a C terminus PI(4,5)P 2 binding site (Maass et al , ). In addition, the activity of ANO1 (De Jesus‐Perez et al , ) and ANO6 (Aoun et al , ; Ye et al , ) is regulated by PI(4,5)P 2 , which prevents channel rundown (De Jesus‐Perez et al , ; Ye et al , ). Therefore, we first determined whether the function of ANO8 requires PM PI(4,5)P 2 by depleting PI(4,5)P 2 with PM targeted 5′‐phosphatase (Korzeniowski et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…A typical PM anchor is PI(4,5)P 2 , and the ANO8 yeast homologue Ist2 has a C terminus PI(4,5)P 2 binding site (Maass et al , ). In addition, the activity of ANO1 (De Jesus‐Perez et al , ) and ANO6 (Aoun et al , ; Ye et al , ) is regulated by PI(4,5)P 2 , which prevents channel rundown (De Jesus‐Perez et al , ; Ye et al , ). Therefore, we first determined whether the function of ANO8 requires PM PI(4,5)P 2 by depleting PI(4,5)P 2 with PM targeted 5′‐phosphatase (Korzeniowski et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…This seems to be close to the site suggested to interact with a phospholipid (modelled as phosphatidic acid; see PDB: 2MKF and 2MKE) in the Rosenbaum, 2017). Given the emerging importance of cholesterol interactions with other ion channels and with receptors(Bukiya and Rosenhouse-Dantsker, 2017;De Jesus-Perez et al, 2018;Lee, 2018) it would not be surprising if cholesterol interactions with TRP channels were of functional importance, although detailed studies of a number of TRP channel family members will be required to establish this. Establishing the interactions of TRP channels with lipids provides an avenue towards defining novel druggable sites on this important class of channel molecules.…”
mentioning
confidence: 99%
“…The inactive PI(4,5)P2 analog diacylglycerol-pyrophosphate has no effect. In whole-cell recording, we also showed that reduction of cellular PI(4,5)P2 by the voltage sensitive phosphatase Dr-VSP or by activation of GPCRs causes a reduction in ANO1 current (31). Pritchard et al (33) have presented biochemical evidence that PI(4,5)P2 binds to ANO1, but they report that exogenous PI(4,5)P2 decreases endogenous Clcurrents thought to be encoded by ANO1 in inside-out patches of pulmonary artery cells, in contrast to the results with heterologously-expressed ANO1 from Ta et al (32) and De Jesus-Perez et al (31).…”
Section: Introductionmentioning
confidence: 60%
“…In addition to being gated by Ca 2+ , ANO1 is also regulated by PI(4,5)P2 (30)(31)(32)(33). Ta et al (32) have reported that PI(4,5)P2 stimulates ANO1 currents in excised patches and we have shown that PI(4,5)P2 abolishes Ca 2+ -dependent inactivation caused by spontaneous PI(4,5)P2 hydrolysis (31). The inactive PI(4,5)P2 analog diacylglycerol-pyrophosphate has no effect.…”
Section: Introductionmentioning
confidence: 99%